2021
DOI: 10.1002/asna.202113903
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental plane of black hole activity for quiescent sources

Abstract: In this work, we construct a sample of black hole X-ray binaries (BH XRBs), low-luminosity active galactic nuclei (LLAGNs), and FR Is with wider distribution of Eddington ratios and re-explore their fundamental plane of BH activities, that is, log L R = X log L X + M log L M BH + c 0. We find that the quiescent BH sources follow a similar fundamental plane (ξ X ∼ 0.6) with sub-Eddington BH sources very well, while the strong radio sources (e.g., FR Is) follow a steeper fundamental plane (ξ X ∼ 1.30). We also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…In addition, most ETG and AGN (∼83%, or 87% if we include radio upper limits) show a radio-to-X-ray radio loudness R X −3.5, classifying these objects as RQ AGN (Terashima & Wilson 2003;Lambrides et al 2020). We found that ETG (most of which have L X < 10 42 erg s −1 and z < 0.5) follow a relation log(L R ) = a log(L X ) + b with a slope a ∼ 0.6, in agreement with fundamental plane studies of low luminosity AGN (slope 0.5 − 0.7, Merloni et al 2003;Dong et al 2021). This slope is commonly interpreted as a signature of inefficient accretion processes, in contrast with what is found for luminous (L X 10 43 erg s −1 ) X-ray-selected local Seyfert galaxies, for which Panessa et al (2015) found a steeper relation (a∼1.1) that is interpreted as a signature of efficiently accreting systems.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, most ETG and AGN (∼83%, or 87% if we include radio upper limits) show a radio-to-X-ray radio loudness R X −3.5, classifying these objects as RQ AGN (Terashima & Wilson 2003;Lambrides et al 2020). We found that ETG (most of which have L X < 10 42 erg s −1 and z < 0.5) follow a relation log(L R ) = a log(L X ) + b with a slope a ∼ 0.6, in agreement with fundamental plane studies of low luminosity AGN (slope 0.5 − 0.7, Merloni et al 2003;Dong et al 2021). This slope is commonly interpreted as a signature of inefficient accretion processes, in contrast with what is found for luminous (L X 10 43 erg s −1 ) X-ray-selected local Seyfert galaxies, for which Panessa et al (2015) found a steeper relation (a∼1.1) that is interpreted as a signature of efficiently accreting systems.…”
Section: Discussionsupporting
confidence: 87%
“…Results are reported in columns 5 and 6 of Table 5. We note that the slope of the ETG correlation (a = 0.58 ± 0.15) is well in the range of the slopes found for low luminosity AGN in the fundamental plane (∼0.5 − 0.7, Merloni et al 2003, see also Dong et al 2021). Such slope values are commonly interpreted as a signature of radiatively inefficient accretion processes (see, e.g., Narayan & Yi 1994;Dong et al 2014, see also Sec.…”
Section: Radio/x-ray Luminosity Correlationssupporting
confidence: 74%
See 1 more Smart Citation
“…The slope will become much steeper with b1.27$$ b\sim 1.27 $$ than radiatively inefficient accretion mode when the x‐ray emissions are dominated by relativistic jet flow (Yuan & Cui 2005). The results of Yuan et al (2009) and Dong, Ge, et al (2021) support the prediction based on the fundamental plane of quiescent sources and radio loud sources. Similar results are also presented by Z.‐Y.…”
Section: Conclusion and Discussionsupporting
confidence: 59%
“…Our main results are summarized as: (1) The Eddington‐scaled Xxray luminosity of our samples covers in the range of LXfalse/LEdd107101$$ {L}_{\mathrm{X}}/{L}_{\mathrm{Edd}}\sim {10}^{-7}-{10}^{-1} $$, which roughly corresponds to a quiescent state, low/hard state, and bright hard state of black hole sources; (2) Blazars and FR Is track a similar and steeper radio–x‐ray correlation F50.3emnormalGHzF2100.3emnormalkeV1.10$$ {F}_{5\kern0.3em \mathrm{GHz}}\propto {F}_{2-10\kern0.3em \mathrm{keV}}^{\sim 1.10} $$; (3) Blazars and FR Is track a steeper fundamental plane of black hole activity ξX1.24$$ {\xi}_{\mathrm{X}}\sim 1.24 $$. Our results are similar to that of Dong, Ge, et al (2021); Dong & Wu (2015), implying that the x‐ray emissions of strong radio black hole sources are from the jet‐dominated flow.…”
Section: Conclusion and Discussionmentioning
confidence: 99%